2021
DOI: 10.1371/journal.pone.0246328
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 associated anxiety enhances tinnitus

Abstract: To investigate if the anxiety associated with coronavirus disease 2019 (COVID-19) is a promoting factor to tinnitus. A retrospective research design collected from 188 tinnitus patients, was used to compare the clinical characteristics of tinnitus between the patients in 2020 under pandemic pressure and those from the matching period in 2019. While anxiety was quantified using the Zung’s Self-rating Anxiety Scale (SAS), tinnitus severity was evaluated using the Tinnitus Handicap Inventory (THI) questionnaire a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 69 publications
0
15
0
2
Order By: Relevance
“…The reported onset or worsening in tinnitus, in both the test and control groups, could also be due to stress and anxiety, whether associated with diagnosis of COVID-19 or as a result of the pandemic (Beukes et al 2020;Xia et al 2021), rather than a direct impact of the virus. It is also possible that the shift from working in a distracting office atmosphere to working from home in a quieter soundscape can increase awareness of the tinnitus.…”
Section: Is Covid-19 Associated With Auditory Symptoms?mentioning
confidence: 99%
“…The reported onset or worsening in tinnitus, in both the test and control groups, could also be due to stress and anxiety, whether associated with diagnosis of COVID-19 or as a result of the pandemic (Beukes et al 2020;Xia et al 2021), rather than a direct impact of the virus. It is also possible that the shift from working in a distracting office atmosphere to working from home in a quieter soundscape can increase awareness of the tinnitus.…”
Section: Is Covid-19 Associated With Auditory Symptoms?mentioning
confidence: 99%
“…Since females have been shown to be more susceptible than males to mental health consequences during the COVID-19 pandemic ( 4 ), an increase in tinnitus severity can be expected particularly in women. Thus, a few cohorts of tinnitus patients have shown an increase in tinnitus severity, assessed through validated questionnaires, possibly promoted by frustration or anxiety ( 9 , 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although this systematic review included 33 studies, many of the research questions remained unanswered. In fact, no study evaluated the impact of the pandemic on the incidence of tinnitus, or on the severity of tinnitus, while changes in tinnitus severity were inferred from the findings of only a few investigations ( 5 , 9 , 10 ). Results were inconclusive on the role of SARS-CoV-2 infection on the occurrence, duration, or severity of tinnitus ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…15 In our study, a difference was found in the THI scores between the pre-and peripandemic periods (p = 0.026), which is in line with the studies that found a relationship between tinnitus and mood. 11,21 Individuals with tinnitus complaints are unhappy, pessimistic, anxious, aggressive, stressed, and depressive due to tinnitus and can express that they have difficulty falling asleep. Tinnitus can prevent these individuals from enjoying life, focusing, and relaxing.…”
Section: Statisticalmentioning
confidence: 99%